2015
DOI: 10.1186/s12884-015-0452-0
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of prepregnancy body mass index and gestational weight gain to adverse neonatal outcomes: population attributable fractions for Canada

Abstract: BackgroundLow or high prepregnancy body mass index (BMI) and inadequate or excess gestational weight gain (GWG) are associated with adverse neonatal outcomes. This study estimates the contribution of these risk factors to preterm births (PTBs), small-for-gestational age (SGA) and large-for-gestational age (LGA) births in Canada compared to the contribution of prenatal smoking, a recognized perinatal risk factor.MethodsWe analyzed data from the Canadian Maternity Experiences Survey. A sample of 5,930 women who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
2
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 34 publications
(38 reference statements)
4
77
2
1
Order By: Relevance
“…This association seemed to depend mainly on higher-quality fat intake and a lower intake of discretionary foods. 3 Dietary quality assessed by an index (score 0-12) designed to indicate intake of fibre, fat and discretionary food, where ≤4 points equals poor dietary quality, 5-8 points fair dietary quality and ≥9 points high dietary quality [22]. 4 Pregnancy requires 500 mg of stored iron.…”
Section: Dietary Quality and Nutritional Intakementioning
confidence: 99%
See 2 more Smart Citations
“…This association seemed to depend mainly on higher-quality fat intake and a lower intake of discretionary foods. 3 Dietary quality assessed by an index (score 0-12) designed to indicate intake of fibre, fat and discretionary food, where ≤4 points equals poor dietary quality, 5-8 points fair dietary quality and ≥9 points high dietary quality [22]. 4 Pregnancy requires 500 mg of stored iron.…”
Section: Dietary Quality and Nutritional Intakementioning
confidence: 99%
“…On the one hand, low GWG increases risk of infant small for gestational age (SGA) [2][3][4] and preterm delivery [1,5]. On the other hand, high GWG increases risk of infant large for gestational age (LGA) [2][3][4], preterm delivery [3], caesarean section (C-section) [5], maternal hypertension [1] and postpartum weight retention [2,6]. Both high and low GWG are associated with higher offspring fat mass during childhood [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies have reported PAFs for pregnancy complications and PTB, as the predominant focus has been on behavioral factors (eg, substance use) . Comparisons to previous research are hindered by study variation.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of preterm birth before 37 weeks was not, or just slightly, increased by maternal obesity, with a population attributable fraction for high BMI of <5% . In contrast, the risk of preterm birth before 33–32 weeks was significantly increased (Table ).…”
Section: Methodsmentioning
confidence: 99%